COMPARISON OF EFFICACY AND SAFETY PROFILE OF EMPAGLIFLOZIN VERSUS DAPAGLIFLOZIN AS ADD ON THERAPY IN TYPE 2 DIABETIC PATIENTS - Hussain, Mazhar; Atif, Moazzam; Babar, Muhammad; Akhtar, Lubna (Journal of Ayub Medical College Abbottabad, 2021)
Background: SGLT-2 (sodium-glucose cotransporter-2) inhibitors are a novel class of oral hypoglycemic agents for the management of type 2 diabetes mellitus (T2DM). Herein, we aimed to assess the efficacy and safety profile of empagliflozin versus dapagliflozin in type 2 diabetic patients Methods: In this randomized controlled trial, type 2 diabetic patients with inadequate glycaemic control HbA1c 7.5-11% with different first line anti diabetic medications were randomly divided in to two groups. Group A were given tablet Empagliflozin 25mg while Group B were given tablet Dapagliflozin 10mg over a period of 12 weeks. The primary end point was to measures efficacy profile in terms of changes in body weight, BMI, fasting blood sugar and HbA1c. The secondary end point was to determine safety and tolerability profile. Results: After 12 weeks of treatment body weight was reduced significantly in both groups empagliflozin -2.9±6.4kg (p‚Œ0.002) versus dapagliflozin -1.7±2.4 (p‚Œ0.007). However, comparison between two groups was non-significant (p‚Œ0.032). FBS was reduced in both study groups empagliflozin -75.6±43.5 mg/dl versus dapagliflozin -63.5±60.5 mg/dl with p< 0.01. However, empagliflozin caused a significant reduction in fasting blood sugar as compared to dapagliflozin (p‚Œ0.001). HbA1c was also significantly reduced in both groups empagliflozin -1.7±0.9% versus dapagliflozin -1.2±1.4% with p<0.01. However, empagliflozin caused a more significant reduction in HbA1c as compared to dapagliflozin (p‚Œ0.002). The tolerability profile of both drugs was quite good and no major adverse effects were reported in both study groups. However minor adverse effects were observed in both study groups. There was low risk of urinary and genital infection with empagliflozin (2.34% & 3.1%) as compared to dapagliflozin (7.08% and 8.66%) with p-value 0.003 and 0.005 respectively. Conclusion: Both empagliflozin and dapagliflozin has excellent efficacy and safety profile. They can be used as add on therapy in type 2 diabetic patients.